LARVICIDAL PROPERTIES OF SIMALIKALACTONE D FROM QUASSIA AFRICANA (SIMAROUBACEAE) BAILL AND BAILL, ON THE MALARIA VECTOR ANOPHELES GAMBIAE - Sama, Woquan; Ajaiyeoba, Edith Oriabure; Choudhary, Mohammed Iqbal (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Botanical and microbial insecticides have been increasingly used for the control of mosquito given their efficacy and documented non-toxic effects on non-target organisms. The discovery of new insecticides is imperative because of the development of resistance by the mosquitoes to the readily available insecticides. The aim of this study was therefore to isolate and characterize compounds from a local medicinal plant, Quassia africana Baill and Baill (Simaroubaceae) that were toxic to Anopheles gambiae.Material and methods:The methanol extracts of the leaves, stem and roots of Quassia africana were tested against fourth instar larvae of An. gambiae. The root extract was partitioned into hexane, chloroform and ethyl acetate and the resulting extracts screened for larvicidal properties. The extracts and the fraction with the highest bioactivity were subjected to repeated column chromatography and isolated compounds evaluated for potential toxicity to An. gambiae larvae. The structure of the active compound was elucidated using spectroscopic techniques. The root extract showed the strongest activity profile (LC50 = 17.58 μg/mL). The chloroform soluble fraction obtained after partitioning the crude extract into solvents based on polarities was the most toxic. Further bio-activity-guided chromatographic separation of the chloroform fraction of the root extract led to the identification and isolation of a simalikalactone D as the larvicidal compound in Q. africana (LC50 = 1.25 μg/mL).Results: Results suggest that Q. africana may serve as a source for vector control agent for malaria.Conclusion: Simalikalactone D was identified as the larvicidal compound in Q. africana (LC50 = 1.25 μg/mL).